Gemuk Tetapi Kurang Gizi: Paradoks Obesitas Anak Rendah Asupan Zat Gizi Mikro - Sugeng Wiyono; Rojali; Miranti (Shofanah Media Berkah, 2026)
Obesity is a disorder characterised by excessive fat accumulation in the body due to an imbalance between energy intake and expenditure. By 2030, it is estimated that 1 in 5 women and 1 in 7 men will be obese (equivalent to more than 1 billion people worldwide). The health effects lead to non-communicable diseases (NCDs) and financial losses totalling £4.47 trillion, five times Indonesia's gross domestic product (GDP) and 170 times total expenditure on health services. The trend in obesity rates is worrying for several reasons. The dangers of obesity in children include obesity in adulthood, stunted growth, psychological disorders, decreased immunity, joint changes, respiratory disorders, impaired academic performance, sexual disorders, and various non-communicable diseases (heart and blood vessel diseases, including diabetes, cardiovascular disease, stroke, and several types of cancer). The study employed a cross-sectional design with a sample size of 50 children. There was no significant association between obesity and micronutrient intake in children; however, the percentage of micronutrient intake below 100% of the RDA was higher in obese children, at 66.6% (fibre), 53.6% (vitamin A), and 59.1% (calcium), respectively. It is recommended to increase the intake of micronutrients in obese children, as well as to prevent obesity by increasing physical activity and reducing energy intake and fatty foods.